Strategi Pengelolaan Kelas di 20 Sekolah Penggerak Kota Semarang - Koidah, Sofiatul; Purnamasari, Iin; Rahmawati, Intan (Pena Edukasia, 2022)
This study aims to describe classroom management strategies in 20 driving schools in the city of Semarang. The research was conducted in 20 primary schools driving the city of Semarang. In this study, qualitative research methods were used with an ethnographic approach and data collection techniques by distributing google form questionnaires. The results showed that the teacher's strategy in managing the class was to condition students before starting learning, arrange student seats, and arrange the beauty of the classroom.